Biological soil crust development affects bacterial communities in the Caragana microphylla community in alpine sandy areas - Zhou, Hong; Li, Lun; Liu, Yunxiang (Frontiers in Microbiology, 2023)
Biological soil crusts (BSCs) constitute a substantial portion of primary production in dryland ecosystems. They successionally mature to deliver a series of ecosystem services. Bacteria, as an important community in BSCs, play critical roles in maintaining the structure and functions of BSCs. However, the process by which bacterial diversity and community are altered with BSC development is not fully understood. In this study, amplicons sequencing was used to investigate bacterial diversity and community compositions across five developmental stages of BSCs (bare sand, microbial crusts, algae crusts, lichen crusts and moss crusts) and their relationship with environmental variables in the Gonghe basin sandy land in Qinghai-Tibet Plateau, northwestern China. The results showed that Proteobacteria, Actinobacteria, Cyanobacteria, Acidobacteria, Bacteroidetes and Firmicutes were predominant in different developmental stages of BSCs, accounting for more than 77% of the total relative abundance. The phyla of Acidobacteria and Bacteroidetes were abundant in this region. With BSC development, bacterial diversity significantly increased, and the taxonomic community composition significantly altered. The relative abundance of copiotrophic bacteria, such as Actinobacteria, Acidobacteria, Bacteroidetes, Verrucomicrobia, Planctomycetes and Gemmatimonadetes significantly increased, whereas the relative abundance of oligotrophic bacteria, such as Proteobacteria and Firmicutes significantly decreased. The relative abundance of Cyanobacteria in the algae crusts was significantly higher than that in the other developmental stages (P < 0.05). Variations in bacterial composition suggested that the potential ecological functions of the bacterial community were altered with BSC development. The functions varied from enhancing soil surface stability by promoting soil particle cementation in the early stages to promoting material circulation of the ecosystem by fixing carbon and nitrogen and decomposing litter in the later stages of BSC development. Bacterial community is a sensitive index of water and nutrient alterations during BSC development. SWC, pH value, TC, TOC, TN, NO3-, TP and soil texture were the primary environmental variables that promoted changes in the bacterial community composition of BSCs.